Performance in a coincidence timing task and stimulus velocity: use of hit rates - Maria Teresa Cattuzzo; Luciano Basso; Rafael dos Santos Henrique; Jorge Sabino Pereira de Oliveira (Universidade Federal de Santa Catarina, 2010)
The aim of this study was to investigate the number of consecutive hits in a complex coincidence timing task, which were used as performance indices, and the effect of light stimulus velocity on reaching these indices. Thirty adults of both genders were tested using an apparatus of coincidence timing for complex tasks and three light stimulus velocities (high, moderate and low). Analysis showed that two performance indices can be used as criteria of performance sta-bilization: three and four consecutive hits in the coincidence goal. Descriptive analysis suggests that the index of consecutive hits should be more rigorous at high light stimulus velocity.